Patient safety culture among health care provider’s in a Tunisian university hospital - Merzougui, Latifa; Sghaier, Sarra; Radaoui, Nedia; Chebil, Dhekra; Turki, Elyes; Majdoub, Wael; Barhoumi, Tarek; Fatnassi, Ridha (International Journal of Infection Control, 2019)
Patient safety is considered a major priority in health care systems. In Tunisia, few attempts have been made since 2011 to evaluate PS culture. The purpose of this study was to measure the patient safety culture level at Ibn El Jazzar hospital in Kairouan, Tunisia. This cross-sectional study was conducted over three months in 2015 in a Tunisian University hospital. The French model of the Hospital Survey On Patient Safety Culture “HSOPSC” was used to explore 10 dimensions of patient safety culture. The survey was distributed to 446 health care providers (physicians and nurses). A score per composite has been calculated. Then the results were compared according to professional categories and work units. The overall average positive response rate for the 10 PS culture composites of the HSOPSC survey was 61.65%. Areas with potential for improvement were overall perception of security (40.73%), leadership (30.9%), organizational learning (41.9%), communication openness (38.3%) and frequency of events reported (33.2%). The area of strength was teamwork within units (58.1%). Non-punitive response to error had the lowest score (29.6%). The comparison of the scores according to professional category showed a significant difference for one composite score, which was the non-punitive answer to the errors particular to nurses (16.3% vs 32.7%; p = 0.020). In contrast, no significant difference between work units was found for all composites scores in our study. Our results demonstrate that patient safety culture remains undeveloped and should be improved at Ibn El Jazzar hospital. Therefore, further studies should be conducted in the context of continuous assessment quality of care.